Brain beta‐amyloid in twin pairs discordant for episodic memory performance: Neuroimaging: Imaging genetics. (7th December 2020) - Lindgren, Noora; Karjalainen, Tomi; Ekblad, Laura L.; Helin, Semi; Karrasch, Mira; Teuho, Jarmo; Tuisku, Jouni; Kaprio, Jaakko; Rinne, Juha O.; Vuoksimaa, Eero
Abstract: Background: β‐amyloid pathology (Aβ) and episodic memory (EM) impairment are biological and cognitive hallmarks of Alzheimer's disease (AD). However, most studies on the Aβ–EM association have been conducted in unrelated individuals and cannot tell if this relationship is confounded by shared genetic and/or environmental effects. We investigated if cortical amyloid pathology‐EM relationship is evident within twin pairs: a design that controls for shared genetic (fully in monozygotic [MZ] and partly in dizygotic [DZ] pairs) and environmental effects. Method: We studied 45 same‐sex (mean [SD] age = 72.9 [4.0] years; 18 women pairs) twin pairs. EM discordance was based on a mean of two verbal delayed free recall measures: Logical Memory and Word List Learning from CERAD‐NB. We also studied within‐pair differences in 3 continuous EM scores (verbal immediate free recall [VerIFR], verbal delayed free recall [VerDFR], and visual delayed free recall [VisDFR]) in relation to within‐pair differences in cortical amyloid pathology. Cortical amyloid pathology in AD signature regions was measured with carbon‐11‐labelled Pittsburgh compound B ([11C]PiB) and quantified as standardized uptake value ratio (SUVR) with cerebellar cortex as a reference region. Result: A total of 42 pairs were discordant for EM (23DZ/19MZ). Twins with poorer EM had higher cortical [11C]PiB SUVR compared to their co‐twins (1.44 vs 1.36), but this difference was not statistically significant (mean intra‐pair difference of 6% / 0.08 SUVR units [95%CI: ‐0.05; 0.20], P =0.23). Using continuous scores within all pairs, co‐twins with higher SUVR had poorer EM scores ( Ps < 0.006): VerIFR (r= ‐0.42), VerDFR (r= ‐0.41) and VisDFR (r= ‐0.46). In DZs, within‐pair differences in EM scores were significantly related to within‐pair differences in SUVR with correlations ranging from ‐0.42 to ‐0.51 ( Ps < 0.05, N=24). In MZs, non‐significant within‐twin pair correlations ranged from ‐0.31 to ‐0.36, ( Ps = 0.11 – 0.16, N=21). Conclusion: By using case‐control twin design we showed that within twin pairs, a co‐twin with higher amyloid pathology had poorer episodic memory. Results suggest that amyloid‐EM relationship is evident when controlling for shared environmental and genetic effects, but studies with larger samples of MZ and DZ twins in different stages of AD continuum are warranted.